2021
DOI: 10.3389/fped.2021.753938
|View full text |Cite
|
Sign up to set email alerts
|

Promelaxin Microenemas Are Non-inferior to Oral Polyethylene Glycol for the Treatment of Functional Constipation in Young Children: A Randomized Clinical Trial

Abstract: Background: Polyethylene glycol (PEG) is recommended as first-line treatment of pediatric functional constipation. However, the oral route of administration is often poorly feasible in children mostly due to poor palatability. Promelaxin microenemas exert a topical evacuative action and may offer a valuable option in pediatric FC.Aim: To assess whether Promelaxin microenemas would be non-inferior to PEG 4000 in young children with FC.Methods: This is a randomized, open-label, multi-centric, non-inferiority tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…1-In improving the benefit/risk ratio of current therapeutics, with a aim of minimal impact on the physiology of the whole body, especially in the long term, and on the environment. 2-In managing the complexity of new diseases and treatments: degenerative, metabolic and functional diseases, as well as multifactorial syndromes, occur at an increasingly higher frequency as the population ages (Van den Berg et al, 2006, Kelishadi 2007, Cockerham et al, 2017, GBD 2015Obesity Collaborators 2017, DeBoer 2019, Cobiac and Scarborough 2021, Dellafiore et al, 2022, Guarino et al, 2022, Nguyen et al, 2022) and often have unsatisfactory or inadequate treatments (Black and Ford, 2021;Strisciuglio et al, 2021;Bousaba et al, 2022;Negi et al, 2022;Singh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…1-In improving the benefit/risk ratio of current therapeutics, with a aim of minimal impact on the physiology of the whole body, especially in the long term, and on the environment. 2-In managing the complexity of new diseases and treatments: degenerative, metabolic and functional diseases, as well as multifactorial syndromes, occur at an increasingly higher frequency as the population ages (Van den Berg et al, 2006, Kelishadi 2007, Cockerham et al, 2017, GBD 2015Obesity Collaborators 2017, DeBoer 2019, Cobiac and Scarborough 2021, Dellafiore et al, 2022, Guarino et al, 2022, Nguyen et al, 2022) and often have unsatisfactory or inadequate treatments (Black and Ford, 2021;Strisciuglio et al, 2021;Bousaba et al, 2022;Negi et al, 2022;Singh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly those with FC, both children and adults, have been the object of multiple studies and various meta-analyses, as shown in Table 3. (Strisciuglio et al, 2021) conducted a randomized noninferiority trial in order to assess whether microenemas of Promelaxin (A complex of honeys + Aloe and Mallow polysaccharides) are not inferior to oral polyethylene glycol (PEG) 4,000 as topical therapy in children with FC according to Rome III criteria (Longstreth et al, 2006). They enrolled infants and young children aged 6-48 months who were randomized to 2 weeks of Promelaxin microenemas or PEG daily, followed by a 6-week ondemand treatment period.…”
Section: Examples Of Randomized and Controlled Studies With Mdmsmentioning
confidence: 99%
“…Several chronic, multifactorial disorders with unsatisfying medical treatment can benefit from MDMS regulation; this is the case of treatment of some gastrointestinal illness (Corazziari, 2020;Bilia et al, 2021) or metabolic disorders (Guarino et al, 2021), even in the pediatric population (Strisciuglio et al, 2021;Stagi, 2022). In this scenario, MDR provides opportunities for therapeutic innovation with complex substances while guaranteeing patients with standards of efficacy and safety.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%